Identification of Potentially Relevant Genes for Excessive Exercise-Induced Pathological Cardiac Hypertrophy in Zebrafish - Zhou, Zuoqiong; Zheng, Lan; Tang, Changfa; Chen, Zhanglin; Zhu, Runkang; Peng, Xiyang; Wu, Xiushan; Zhu, Ping (Frontiers in Physiology, 2020)
Exercise-induced cardiac remodeling has aroused public concern as sudden cardiac death has threatened the life of athletes for a long time, but little is known about the underlying mechanism of sports induced cardiac injury. In this study, we established an excessive exercise-induced pathological cardiac hypertrophy model in zebrafish with increased myocardial fibrosis, myofibrils disassembly, mitochondrial degradation and upregulated expression level of the pathological hypertrophy maker genes in heart. High throughput RNA-seq analysis revealed that the differentially expressed genes were enriched in the regulation of autophagy, protein folding and degradation, myofibril development, angiogenesis, metabolic reprogramming, insulin and FoxO signaling pathway. The FOXO proteins may be the core mediator of the regulatory network to promote the pathological response. Further, PPI network analysis showed that pik3c3, gapdh, fbox32, fzr1, ubox5, lmo7a, kctd7, fbxo9, lonrf1l, fbxl4, nhpb2l1b, nhp2, fbl, hsp90aa1.1, snrpd3l, dhx15, mrto4, ruvbl1, hsap8b and faub are the hub genes that correlated to the pathogenesis of pathological cardiac hypertrophy. The underlying regulatory pathways and cardiac pressure responsive molecules uncovered in this study will provide valuable hints for the supervision and clinical treatment of pathological cardiac hypertrophy induced by improper exercise training.